Body Part Insurance for Football Athletes Abroad Reviewed under Positive Law in Indonesian - Katarina, Katarina; Sulistiyowati, Deny; Maedy, Maedy (Jurnal Indonesia Sosial Sains, 2025)
This article analyzes insurance related to human body parts for football athletes abroad compared to positive laws in Indonesia. This insurance product is a potential product to be explored because of the various types of professions that are developing in this country, especially professional athletes who take part in the sport of football. However, it is unfortunate that up to now there are no regulations or insurance products that can be used to fulfill this kind of request. The aim of this research is to compare human limb insurance for football athletes in other countries with existing regulations in Indonesia. The research method used is normative juridical with comparative approach using primary legal materials, secondary legal materials and interviews. In conclusion, the rules regarding insurance for body parts are contained in article 1 number 25 of Law No. 40 of 2014 concerning Insurance. The object of agreement on the body parts of professional soccer athletes is the feet. The principles used in insurance contract law emphasize the principle of consensualism, freedom of contract and good faith. Insurance companies in Indonesia should take this potential and translate it into a new insurance product using the principle of insurable interest and the principle of indemnity like in other countries. The use of this type of life insurance can be used for insurance for the limbs of football athletes such as in Italy, Belgium, Spain, the Netherlands or loss insurance according to insurance in South Africa, Germany, France, Belgium and England.